Relation between student’s perceptions to the statistics lecturer in learning process with statistics achievement - Nasir, A. Muhajir; Hasmar, Dian Hardianti (Malikussaleh Journal of Mathematics Learning (MJML), 2018)
This is ex post facto research to find the relation between student’s perceptions to the statistics lecturer in learning process with statistics achievement of students semester V of the Department of Mathematics Education of Universitas Muslim Maros. The population is all students of the Department of Mathematics Education Universitas Muslim Maros in academic year 2017/2018. And the sample is 30 respondents of students who taught by statistics lecturer. Data analyze by SPSS software. According to analyze get that student’s perception to statistics lecturer generally very positive with average 138,57 and statistics achievement is very good with average 79,63. Besides that, inferential show that there is relation between student’s perceptions to the statistics lecturer with coefficient is 0,594. From analyze, it can conclude that there are relation between student’s perceptions to the statistics lecturer in learning process with statistics achievement of students semester V of Department of Mathematics Education Universitas Muslim Maros.